2015
DOI: 10.1038/srep12166
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive measurement of huntingtin protein in cerebrospinal fluid demonstrates increase with Huntington disease stage and decrease following brain huntingtin suppression

Abstract: Quantitation of huntingtin protein in the brain is needed, both as a marker of Huntington disease (HD) progression and for use in clinical gene silencing trials. Measurement of huntingtin in cerebrospinal fluid could be a biomarker of brain huntingtin, but traditional protein quantitation methods have failed to detect huntingtin in cerebrospinal fluid. Using micro-bead based immunoprecipitation and flow cytometry (IP-FCM), we have developed a highly sensitive mutant huntingtin detection assay. The sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 33 publications
2
106
1
1
Order By: Relevance
“…Shortly afterwards, Southwell and colleagues reported mHTT quantification in CSF with immunoprecipitation and flow cytometry (IP-FCM) using a combination of MW1 and HDB4E10 antibodies, the latter recognizing a C-terminal binding site [84]. In a single cohort, overlapping with the Vancouver dataset from our work, they confirmed the presence of mHTT in mutation carriers but not controls and a tendency to rise with onset and clinical manifestations.…”
Section: Mutant Huntingtinsupporting
confidence: 70%
“…Shortly afterwards, Southwell and colleagues reported mHTT quantification in CSF with immunoprecipitation and flow cytometry (IP-FCM) using a combination of MW1 and HDB4E10 antibodies, the latter recognizing a C-terminal binding site [84]. In a single cohort, overlapping with the Vancouver dataset from our work, they confirmed the presence of mHTT in mutation carriers but not controls and a tendency to rise with onset and clinical manifestations.…”
Section: Mutant Huntingtinsupporting
confidence: 70%
“…Although singleplex and multiplex immunoprecipitation detected by flow cytometry can be highly sensitive down to the femtomole to attomole analyte range (2325), application of this technology to multiprotein complexes in signal transduction required the investigation of biostatistical analysis techniques. The present investigation involved the comparison of several statistical approaches using both empirical and computer-simulated experimentation to select an applicable statistical approach for PiSCES analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This ASO and others have undergone further development and improvement for human application to increase the specificity of the ASO to greater than 100-fold for mutant Htt allele over normal allele (Ostergaard et al, 2013). When evaluated in Hu97/18 mice exhibiting expression of both the mutant and wildtype Htt allele, specificity for the mutant allele was confirmed with specific reduction of mutant Htt without change to the normal mRNA or protein (Southwell et al, 2015) and demonstrated an extended duration of action from 16 to 32 weeks depending on the 2′ modification (Skotte et al, 2014). Whether these impressive qualities afford a therapeutic effect for modulating locomotor or cognitive deficits in HD mouse models remains to be determined.…”
Section: Application To Neurodegenerative Diseasesmentioning
confidence: 93%